Effect of anhydrous ethanol/gasoline blends on performance and exhaust emissions of spark-ignited non-road engines - Ribeiro, Camilo Bastos; Martins, Kelly Geronazzo; Diniz Gueri, Matheus Vitor [UNESP]; Pavanello, Guilherme Pozzobom; Schirmer, Waldir Nagel (Springer, 2018)
Ethanol is a renewable fuel and it is considered an alternative to gasoline in Otto-cycle engines. The present study evaluated the behavior of exhaustion gas carbon monoxide (CO) and total hydrocarbons (THC) according to the levels of anhydrous ethyl alcohol (AEA) added to gasoline in different proportions (E0, E10, E20, E27, that is, pure gasoline and its blends with AEA at 10, 20, and 27% v/v) in the use of non-road single cylinder engines of different powers (13 and 6.5 hp), to the loads applied to engine-generators and the air-fuel ratio (A/F) admitted to the engine cylinders. Also, the performance of engine-generators was verified in terms of mass, specific and energetic consumption and efficiency of the evaluated systems for the same blends and loads. The results showed that an increase in the AEA content in the blend resulted in significant drops in CO and THC concentrations for both engine-generators, while fuel consumption showed a slight upward trend; the increases in applied loads resulted in an increase in CO and THC concentrations and fuel consumption. In general, a higher AEA content (oxygenated) in the blends had a greater effect on gaseous emissions compared to the effect on consumption and system efficiency.
Keywords: Biofuels; Combustion assays; Exhaust emissions; Otto-cycle engines; Oxygenated additive; Renewable energy